IoT solution information security certification conceptual framework: On improving the transparency and accountability of IoT Solutions through an Open World perspective - Duarte, Luiz Otavio; Prestes, José Augusto de Lima (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The rapid growth of Internet of Things (IoT) solutions development and the rise of agile development utilization, combined with the so-called “low touch economy” and the recent discussions on privacy and data protection brought several demands related to Information Security. Despite the existence of several efforts – either academic or not – focused on the definition and implementation strategies for certification of Information Security models designed for Information Technology and Communications (ICT) solutions, these aren't widely adopted. In addition, there are significant differences between typical IoT solutions and ICT solutions as traditionally presented, which ends up demanding different certification strategies. Continuous and more dynamic certification models (using cutting edge technologies such as blockchain, self-regulation, analytics, and artificial intelligence) are demanded in this context. This work discusses more effective forms of certification, using innovative edge concepts and technologies, at first aiming to identify a set of inhibiting factors, offenders, challenges or issues that need to be addressed correctly when developing an effective large-scale security certification model.